EFEK PILATES TERHADAP DAYA TAHAN OTOT ABDOMINAL PADA ATLET OLAHRAGA POPULER DI INDONESIA : Literature Review - Nida Fadhilah (2020)
Muscle endurance, especially the Abdominal, is important for athletes to be able to maintain the best performance during training and when competing for long periods. This writing aims to determine the effect of Pilates on endurance of the Abdominal muscles in popular sports's athletes in Indonesia. The method used in this research is literature review. Literature review's carried out using software such as Google Scholar, SciELO, PEDro, and Researchgate using keywords in years between 2015-2020. The search results found 4 journals that match the inclusion criteria. Pilates given to 16 samples shows a significant value, p <0.001 Curl Up Test CG 2.174, EG 3,521. After a journal review, it was concluded that Pilates has an influence on increasing Abdominal muscle endurance in popular sports athletes.